Historical Features of the Social Rehabilitation of the Blind - Andrejauskas, Vladas (Problemos, 1974)
In the article the idea is developed that social conditions are the decisive factor stipulating consequences of blindness. Analysing historical facts which characterize changes in the attitude of community towards the blind and in their social status and largely referring to the capitalist and socialist reality the author shows that the attitude of community towards the blind historically is changing for the better, i.e., towards rehabilitation and acknowledgement of their full social value. Objective prerequisites for realizing full social value of the blind developing their abilities and activity, compensation of their physical defect are created only under conditions of socialism, when private property of means of production, competition, unemployment are abolished, when man really turns to be the greatest value.